Influences of Two Land-Surface Schemes on RegCM4 Precipitation Simulations over the Tibetan Plateau - Xuejia Wang; Meixue Yang; Guojin Pang (Advances in Meteorology)
The effects of different RegCM4 land-surface schemes on Tibetan Plateau (TP) precipitation simulations were investigated. Two groups of ten-year (1992–2001) simulation experiments (hereafter referred to as BATS and CLM) were performed based on two land-surface schemes (BATS and CLM3.5, resp.) and were compared with observed data using the same domain, initial, and lateral boundary conditions, cumulus convective scheme, and spatial resolution. The results showed that the CLM monthly precipitation more closely matched the observed data compared with BATS. BATS and CLM both overestimated summer precipitation in the northern TP but underestimated summer precipitation in the southern TP. However, CLM, because of its detailed land-surface process descriptions, reduced the overestimated precipitation areas and magnitudes of BATS. Compared to CN05, the regional average summer precipitation in BATS and CLM was overestimated by 34.7% and underestimated by 24.7%, respectively. Higher soil moisture, evapotranspiration, and heating effects in the BATS experiment triggered changes in atmospheric circulation patterns over the TP. Moreover, BATS simulated the lower atmosphere as warmer and more humid and the upper atmosphere (~150 hPa) as colder than the CLM simulations; these characteristics likely increased the instability for moist convection and produced more summer precipitation.